Dinámica de las aguas en la parte interna del Golfo de Nicoya ante altas descargas del Río Tempisque - Lizano, Omar G. (Revista de Biología Tropical, 1998)
The water dynamics of the upper part of the Gulf of Nicoya were studied under high discharges of the Tempisque river. The salinity values close to freshwater found north of Chira island are the lowest reported for this lone. and have importance in mariculture planing. A salinity gradient is developed during low tide, indicating a strong stratification in the inner Gulf. High freshwater river discharge is coup led with an upstream bottom flow (sail wedge) that reacher; the head of the estuary. Under high river discharges, surface and bottom salinity values are correlated with depth, where vertical shear and tidal pumping must explain the high salinity values found in the bottom inward flow. A fish distribution pattern is proposed based on the observed salinity distribution and some field data. Salinity gradients appear to influence the concentration of fish in several relatively deep areas in the inner Gulf of Nicoya.